2016
DOI: 10.1186/s12933-016-0339-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a causal relationship between high serum adiponectin levels and increased cardiovascular mortality rate in patients with type 2 diabetes

Abstract: BackgroundDespite its beneficial role on insulin resistance and atherosclerosis, adiponectin has been repeatedly reported as an independent positive predictor of cardiovascular mortality.MethodsA Mendelian randomization approach was used, in order to evaluate whether such counterintuitive association recognizes a cause-effect relationship. To this purpose, single nucleotide polymorphism rs822354 in the ADIPOQ locus which has been previously associated with serum adiponectin at genome-wide level, was used as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 54 publications
1
30
4
3
Order By: Relevance
“…The Dallas heart study revealed that higher adiponectin level is associated with increased mortality and cardiovascular morbidity in a young, multiethnic population across all subgroups defined by age, gender, race, obesity, diabetes, MS, or elevated high-sensitivity C-reactive protein. The similar findings were recently detected in hemodialysis and diabetic patients [8][9][10]. These findings are paradoxical considering the fact that large studies showed that adiponectin inversely correlated with insulin and HOMA indexindex of insulin resistance [11].…”
Section: Introductioncontrasting
confidence: 42%
“…The Dallas heart study revealed that higher adiponectin level is associated with increased mortality and cardiovascular morbidity in a young, multiethnic population across all subgroups defined by age, gender, race, obesity, diabetes, MS, or elevated high-sensitivity C-reactive protein. The similar findings were recently detected in hemodialysis and diabetic patients [8][9][10]. These findings are paradoxical considering the fact that large studies showed that adiponectin inversely correlated with insulin and HOMA indexindex of insulin resistance [11].…”
Section: Introductioncontrasting
confidence: 42%
“…This finding is in marked contrast with our recent report, showing a significant association between rs832354 (a single nucleotide polymorphism strongly associated with HMW adiponectin 3 ) and cardiovascular mortality in type 2 diabetes mellitus patients of both sexes. 4 Of note, our association was entirely driven by males (ie, no association observed among females), 5 thus coincidentally reinforcing the belief of a sexual dimorphic effect of serum adiponectin on cardiovascular mortality 2 and further stressing the difference with Liu et al 1 report. Here, we address some possible causes of such strident discrepancy.…”
Section: To the Editormentioning
confidence: 52%
“…In fact, HPFS patients were recruited from all over the United States, whereas ours were all recruited in a very small and homogeneous region of Central Southern Italy. In addition, whereas our participants were all Whites, 4 those of HPFS were not. 1 Because genetic background of serum adiponectin is heterogeneous across ethnicities, 6 such difference too may have contributed to discrepancy between the 2 studies.…”
Section: To the Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Антисклеротическое действие адипонектина включает в себя стимуляцию пролифе-рации эндотелия, ингибирование пролиферации и миграции гладкомышечных клеток сосудов, подав-ление экспрессии в эндотелии молекул адгезии. Вме-сте с тем, есть исследования с противоположными результатами [9][10][11][12].…”
Section: Secretory Biomolecules Of Visceral Adipocytes Associations Wunclassified